New insights on tidal dynamics and tidal energy harvesting in the Alderney Race. (21st August 2020) - Sentchev, Alexei; Thiébot, Jérôme; Bennis, Anne-Claire; Piggott, Matthew
Abstract : The Introduction presents motivations, significance and some key points of the research activities performed in the Alderney Race. This article is part of the theme issue 'New insights on tidal dynamics and tidal energy harvesting in the Alderney Race'.